A methodology based on insecticide impregnated filter paper for monitoring resistance to deltamethrin in Triatoma infestans field populations. Issue 4 (2nd August 2017) - REMÓN, C.; LOBBIA, P.; ZERBA, E.; MOUGABURE‐CUETO, G.
Abstract: The domiciliary presence of Triatoma infestans (Klug) (Hemiptera: Reduviidae) after control interventions was reported in recent years. Toxicological studies showed high levels of resistance to pyrethroids suggesting resistance as one of the main causes of deficient control. The aim of the present study was to develop a protocol to test resistance to deltamethrin in T. infestans collected from the field by discriminate concentration. To evaluate field insects, the effect of age (early vs. later) and nutritional state (starved vs. fed) on the deltamethrin susceptibility of each developmental stage was studied. Topical and insecticide impregnated paper bioassays were used. Using the impregnated paper, the susceptibility to deltamethrin was not affected by the age of the stadium and the nutritional states, and varied with the post‐exposure time and with the different developmental stages. A discriminant concentration of deltamethrin (0.36% w/v) impregnated in filter paper was established for all developmental stages. Finally, the methodology and the discriminant concentration were evaluated in the laboratory showing high sensitivity in the discrimination of resistance. The present study developed a methodology of exposure to insecticide impregnated papers and proposes a protocol to test T. infestans in field populations with the aim to detect early evolution of resistance to deltamethrin.